Transcranial Motor Evoked Potentials during Spinal Deformity Corrections—Safety, Efficacy, Limitations, and the Role of a Checklist - Acharya, Shankar; Palukuri, Nagendra; Gupta, Pravin; Kohli, Manish (Frontiers in Surgery, 2017)
Introduction: Intraoperative Neurophysiological monitoring (IONM) has become a standard of care in spinal deformity surgeries to minimize the incidence of new onset neurological deficit. Stagnara wake up test and ankle clonus test are the oldest techniques described for spinal cord monitoring, but they cannot be solely relied upon as a neuromonitoring modality. Somatosensory evoked potentials (SSEPs) monitor only dorsal tracts and give high false positive and negative alerts. Transcranial motor evoked potentials (TcMEPs) monitor the more useful motor pathways. The purpose of our study was to report the safety, efficacy, limitations of TcMEPs in spine deformity surgeries and the role of a checklist. STUDY DESIGN: Retrospective review of all spinal deformity surgeries performed with TcMEPs from 2011-2015. Material and Methods: All patients were subjected to IONM by transcranial electrical motor evoked potentials (TcMEPs) during the spinal deformity surgery. Patients were included in the study only if complete operative reports and neuromonitoring data and post-operative neurological data were available for review. An alert was defined as 80% or more decrement in the MEP amplitude, or increase in threshold of 100 V or more from baseline. The systemic and surgical causes of IONM alerts and the postoperative neurological status were recorded. Results: Total 61 patients underwent surgery for spinal deformities with TcMEPs. The average age was 12.6 years (6-36 years), and male: female ratio was 1: 1.3. Diagnoses included idiopathic scoliosis (n=35), congenital scoliosis (n=13), congenital kyphosis (n=7), congenital kyphoscoliosis (n=4), post-infectious kyphosis (n=1), and post-traumatic kyphosis (n=1). The average kyphosis was 72° (45°-101°) and the average scoliosis was 84° (62°-128°). There were total 33 alerts in 22 patients (36%). The most common causes were Hypotension (n=7), drug induced (n=5), deformity correction (n=5), osteotomies (n=3), tachycardia (n=1), screw placement (n=2) and electrodes disconnection (n=1). Reversal of the inciting event cause resulted in complete reversal of the alert in 90% of the times. Three patients showed persistent alerts, out of whom one had a positive wake up test and woke up with neurodeficit, which recovered over few weeks, while the other patient showed persistent alerts but woke up without any deficit. Sensitivity and